2020
DOI: 10.1186/s12870-020-2284-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of differentially expressed genes in cytoplasmic male-sterile line and its fertility restorer line in pigeon pea (Cajanus cajan L.)

Abstract: Background: Pigeon pea (Cajanus cajan L.) is the sixth major legume crop widely cultivated in the Indian sub-continent, Africa, and Southeast Asia. Cytoplasmic male-sterility (CMS) is the incompetence of flowering plants to produce viable pollens during anther development. CMS has been extensively utilized for commercial hybrid seeds production in pigeon pea. However, the molecular basis governing CMS in pigeon pea remains unclear and undetermined. In this study transcriptome analysis for exploring differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 150 publications
(186 reference statements)
2
16
0
Order By: Relevance
“…Based on GO, BiNGO, and KEGG analysis we could establish a possible connection of CMS trait of pigeonpea with perturbations in glucose and lipid metabolism, energy deficiency, pollen development and pollen tube growth, and ROS generation and PCD. Our findings are congruent with a previous report in pigeonpea (Saxena et al., 2020) and similar mechanisms reported in other crops. Our findings offer a comprehensive foundation to accelerate functional genomics of CMS trait of pigeonpea.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Based on GO, BiNGO, and KEGG analysis we could establish a possible connection of CMS trait of pigeonpea with perturbations in glucose and lipid metabolism, energy deficiency, pollen development and pollen tube growth, and ROS generation and PCD. Our findings are congruent with a previous report in pigeonpea (Saxena et al., 2020) and similar mechanisms reported in other crops. Our findings offer a comprehensive foundation to accelerate functional genomics of CMS trait of pigeonpea.…”
Section: Discussionsupporting
confidence: 94%
“…(2017) also associated pollen viability in pigeonpea with impairments in boron homeostasis, which concurs with our observation on differential expression of boron transporters ( C.cajan_04911, C.cajan_39524 ) between the two lines. Consistent with earlier reports, we observed lower expression of arabinogalactan glycoproteins (AGPs), such as GPI‐anchored proteins and Fasciclin‐like arabinogalactan protein 3, in the CMS line, suggesting their participation in impaired microspore development (Rhee et al., 2015; Saxena et al., 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies also reported that the AP2 gene family is highly active in pollen fertility in various plants. However their specific gene functions and regulatory networks are yet to be investigated [54,55]. The bHLH proteins bind to the specific DNA target sites and play a critical role in programmed cell death (PCD) and pollen development [56].…”
Section: Discussionmentioning
confidence: 99%
“…Male sterility is a common phenomenon in flowering plant species, occurring in several crops (Liu et al, 2014;Li et al, 2016;Chen et al, 2020b;Saxena et al, 2020). Flowering plants require normal anther dehiscence to ensure timely pollen release at fruit-setting stages.…”
Section: Ghpld Genes May Mediate Anther Dehiscence In Cottonmentioning
confidence: 99%